Application of Pavement Management Systems for the Nicosia Turkish Municipality Road Network - Ulunay, Deniz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Pavement management systems are used throughout the world to restore and maintain a country’s pavements to better serve communities. This thesis aimed to identify existing rehabilitation and management techniques and examine the work of the Nicosia Turkish Municipality as a case study. In addition, using a condition survey, this thesis explored main challenges pertaining to the Nicosia road network, propose relevant rehabilitation works, and calculate associated costs. Briefly, the main problems of the Nicosia road network were identified using QGIS. Associated rehabilitation costs for the pavements were calculated using the 2016 costbook, the most up-to-date costbook available at the commencement of this thesis. The roads were categorised, using specific color codes, according to their construction date. The results of the condition survey were analysed and relevant recommendations were made for a better pavement system. The current conditions of the pavements were discussed alongside the rehabilitation and maintenance techniques. The Pavement Condition Index for each road were calculated and the current budget for the reconstruction, rehabilitation, and maintenance of the roads were considered in view of effective rehabilitation and maintenance techniques. Graphs, charts and tables were used to illustrate the data produced in this research. It was concluded that the current budget of the Nicosia Turkish Municipality does not provide sufficient maintenance and rehabilitation. The current budget should be almost doubled in order to provide better maintenance and rehabilitation services for the community. Therefore, the living standards of the citizens will improve while both individual and public transportation will become faster and safer. Uniquely, this thesis constitutes the first research study on Nicosia road network.

ÖZ: Günümüzde yol yapım çalışmaları günlük hayatı kolaylaştırmakla birlikte, ilgili birimlerin halka karşı olan sorumluluklarını yerine getirerek halka hizmet etmelerini kolaylaştırmaktadır. Düzgün ve kullanılabilir yollara sahip olan ülkelerdeki yaşam standartlarının diğerlerine kıyasla daha yüksek olduğu yadsınamaz bir gerçektir. Bu çalışma, KKTC'nin başkenti olan Lefkoşa'daki yolların durumlarını ele alarak Lefkoşa Türk Belediyesi'nin sorumluluğunda olan yolların durumunu QGIS programı vasıtası ile veri haline getirmiştir. Araştırmacı bu çalışmanın amacına hizmet edebilmesi adına Lefkoşa'daki yolların durumunu birebir ziyaret ederek kaydetmiş ve bu yolları iyileştirebilmek adına önerilerde bulunmuştur. Bu bağlamda, yollar bozukluk seviyeleri ve trafik yoğunluğuna göre sınıflandırılarak iyileştirme yönündeki çalışmalarda öncelik hakkının hangi yolda olması gerektiği konusunda sonuçlara varılmıştır. Araştırmacı bu sonuçları tablo ve grafikler halinde sunulmaya hazırlayarak daha kolay bir anlaşılırlık sunmuştur. Yapılan çalışma sonucunda, Lefkoşa Türk Belediyesi'nin mevcut mali bütçesinin yol çalışmaları için yetersiz kaldığı kanısına varılmıştır. Etkili yol çalışmaları için mali bütçenin neredeyse iki katına çıkarılması gerektiği ve böylelikle halkın daha etkili bir yol hizmetine erişebileceği sonucu çıkarılmıştır. Bununla birlikte, hem özel hem de toplu taşımacılıkta daha hızlı ve daha güvenli ulaşım sağlanacaktır. Literatürde yapılan taramada Lefkoşa bölgesine özgün bir çalışmaya rastlanmamıştır ve çalışma orjinalite bakımından özgünlüğünü korumaktadır.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Supervisor: Assist. Prof. Dr. Mehmet Metin Kunt.
Keywords: Civil Engineering; Traffic Engineering; Pavements--Maintenance and repair--Management--Nicosia--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Nicosia Turkish Municipality; Nicosia; pavement; rehabilitation and management